Digital transformation’s applications on higher education learning - Freire, José Miguel Correia de Araújo (2022)
BACKGROUND – Higher Education Institutions (HEI) have mainly used technology to incrementally innovate their sector, in lieu of disrupting HEI programming altogether (Jackson, 2019). However, Navaridas-Nalda et al. (2020) identify the need to digitally transform education as a “core concern” and an “educational priority”. AIM – To discover how HEI can take advantage of Digital Transformation to enhance students’ learning outcomes. METHODOLOGY – Design Science Research (DSR) with focus groups. A Literature review was conducted and through it, a conceptual framework of digital transformation in HEI was created, which was then subjected to validation through two focus groups. RESULTS / FINDINGS – Reflections from the focus groups and a proposal of the final iteration of the framework are presented. ISCTE-IUL is used as a case study for an application of the framework. CONCLUSION / SIGNIFICANCE – HEI must create a digital culture that directs it toward the investigation of newer ways of providing student-oriented solutions. To offer valuable and disruptive educational experiences, HEI will have to modernize teaching, assessment and certification. Digital transformation has brought new elements that can bolster teaching, such as digital platforms and contents and innovative educational methodologies and the use of these resources can enable more customized, self-regulated, collaborative and stimulating learning (Benavides et al., 2020). This dissertation’s significance rests upon the conceptual framework it presents. ORIGINALITY / VALUE – Kerroum et al. (2020) have identified that digital transformation hasn’t been used to create a framework that can be adopted by a traditional HEI. This dissertation addresses this opportunity.